Materialist Science: The Negative Science (American Journal of Islam and Society, 1995)
It is commonly believed that physical phenomena can be understoodin scientific terms. Science is presumed to produce knowledge that enablesman to predict future events, control his environment or explain diversephenomena. Regardless of the use to which scientific knowledge is put,the cognitive claim is there. The question is: Do scientific results constituteknowledge? To answer this question, it is necessary to examine thelogical structure of science. The problem is one of justification. Given thata conclusion is supported by scientific evidence, is the scientific conceptof evidence a legitimate one? These questions about the foundation of scientificinference (i.e., the scientific method of justification) have greatimport.The methods of inference taught in the Qur'an are distinct from and inconflict with those of science. Furthermore, we believe that the applicationof the Qur'anic methods will yield knowledge of God, which is theonly true knowledge. However, the successes of science and its technologicalconsequences have made many people, including believers in God,equate knowledge with scientific knowledge. There are many who stillhold that religion is a matter of faith-the "dogmas" of religion are acceptedon faith. The point is that the grounds for accepting a faith have nothingto do with cognitive claims. If a particular religion is fundamentally amatter of faith, then there is no basis for pref erring it to other faiths.In the face of this conflict between the method of the Qur'an and thatof science, it is essential to assess the cognitive claims of religion. If ourcommitment to religion is to be more than an unjustified devotion, wemust know that revelation is better suited to the attainment of knowledgethan science. The problem is to ascertain whether there are sound logicalreasons for supposing that the conclusions of revelation constitute morereliable, in fact the reliable knowledge, than conclusions established on thebasis of the scientific method of inferences.Why and How Questions: An Artificial DivisionScience is based on causality, the cornerstone of materialism and theantithesis of God's Oneness (tawbid). For this reason, if the scientific ...